Comparison between spousal donor transplantation treated with anti-thymocyte globulin induction therapy and, living related donor transplantation treated with standard immunosuppression - Erkan Demir; Saime Paydas; Ugur Erken (Saudi Journal of Kidney Diseases and Transplantation, 2014)
The worldwide shortage of organs available for transplantation has led to the use of living-unrelated kidney donors. In this context, spouses represent an important source of organ donors. We compared the allograft outcomes of spousal donor transplantation (SDT) with anti-thymocyte globulin (ATG) induction therapy and living related donor transplantation (LRDT) with triple immonosuppression and basiliximab, in addition. Among the 335 living and deceased donor kidney transplantations performed between April 2001 and June 2010, there were 274 living donor kidney transplantations including 34 SDT and 240 LRDT. The minimum follow-up period was 36 months. All recipients of SDT received ATG (1.5 mg/kg) induction therapy, which was stopped five to seven days after surgery. Maintenance immunosuppression included tacrolimus (TAC), mycophenolate mofetil (MMF) and prednisolone. LRDT recipients received triple immunosuppressive protocol consisting of cyclosporine or TAC, MMF and prednisolone, in addition to basiliximab. There was a significant difference between the two groups in recipient age, while pre-operative duration on dialysis, recipient sex and donor age and sex were not significantly different. There was also a significant difference between the two groups in the number of human leukocyte antigen (HLA) mismatches. The 1-, 3- and 5-year graft survival rates of SDT were 94.1%, 88.2% and 79.4%, respectively, and the frequency of acute rejection episodes was 5.8% (two cases). The 1-, 3- and 5-year graft survival rates of LRDT were 95.8%, 91.6% and 83.3%, respectively, with the frequency of acute rejection being 16.2%. The graft survival rates of SDT were as good as LRDT, while the acute rejection rates in SDT were lower than in LRDT, although the difference was not statistically different (P = 0.13).